The protection of cultural heritage in the International Criminal Courts - Stryjkowska, Sylwia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The article aims to present the problem of the ineffectiveness of international legal instruments for the protection of cultural heritage. It presents examples of where such laws were violated and suggests that international criminal law can contribute to a better condition of cultural property. The author emphasizes that the International Criminal Court should play an important role in safeguarding such property from destruction in the future. In that context, the article presents inter allia the case of Ahmad Al Faqi Al Mahdi, which is claimed to be a milestone in the protection of cultural heritage.